Effects of different homeopathic potencies of Cephalendra indica in treatment of neuropathic pain in streptozotocin induced diabetes - Lalit Kishore; Randhir Singh (Faculty of Pharmacy, Cairo University, 2017)
Hyperglycemia and oxidative stress are involved in the development of diabetic neuropathy (DN). This study was designed to evaluate the effect of homeopathic preparation of Cephalendra indica (family Cucurbitaceae) mother tincture (MT), 6 C and 30 C potencies on DN in wistar rats. DN was induced by intraperitoneal injection of streptozotocin (60Â mg/kg) 15Â min after nicotinamide (230Â mg/kg, i.p.) administration. Rats were divided into six groups (nÂ =Â 6). Group 1 and 2 were kept normal control and diabetic control respectively whereas groups 3â5 consist of DN rats treated with different doses of C. indica MT, 6 C and 30 C potencies for 30Â days. Gabapentin (30Â mg/kg) was used as standard. DN was assessed by thermal (hot plate and tail immersion method) and mechanical hyperalgesia (randell-sellito analgesiometer test), allodynia (von frey hair test), motor nerve conduction velocity (MNCV) and oxidative-nitrosative stress in streptozotocin induced experimental diabetes Tissue antioxidant enzymes (SOD, GSH, TBARS) level was measured to assess the oxidative stress. Also the level of advanced glycation end products (AGEs) in sciatic nerve along with nitrite estimation was determined. MT, 6 C and 30 C potencies of C. indica produced significant attenuation in the biochemical parameters used to assess DN. Moreover, oxidative stress and AGEâs level in sciatic nerve was also found to be significantly reduced. So, it can be concluded that homeopathic potencies of C. indica have protective effect against DN via inhibition of oxidative stress and AGEâs. Keywords: Diabetic neuropathy, Hyperglycemia, Cephalendra indica, Oxidative stress, AGEâs